What should every woman know about the kitchen? Theoretical considerations in the light of the nineteenth-handbooks for young women - Raińska, Kinga (Perspektywa stołu, 2023)
The guide literature presented a very idealized vision of the cooking skills of nineteenth-century housewives. In fact, there were many ladies, especially in very wealthy courts, who prided themselves on never crossing the kitchen doorstep. In this era, it was believed that the future housewife should become thoroughly familiar with the kitchen, which did not mean that she should know how to cook. On the contrary, she hardly ever prepared the dishes herself. She was only supposed to have general knowledge about how individual dishes should be prepared, what products should be used for them, ensuring that the appropriate amount of food was delivered from the pantry or the necessary products of appropriate quality were purchased. She should also be able to give appropriate orders to the cook, arrange the menu, ensure punctuality at the table or make sure that her orders are properly carried out. In short, she should be able to manage all matters related to the kitchen. Of course, it was welcome for the housewife or her daughters to be able to prepare at least one dish by themselves, but usually it was a dish for special occasions. Usually housewives were assisted by housekeepers in their kitchen activities, as well as by residents, who often devoted most of their time to housework. As a result of changes in the social structure that took place in the second half of the nineteenth century, many women, even those from the highest social classes, began to be interested in the cuisine. More and more importance began to be paid to the quantity and quality of consumed food. Taking care of the kitchen, the appearance and behavior at the table, supervising cooking or personal preparation of dishes began to be identified with the so-called a good tone, without which it was impossible to pass by indifferently.